Biodegradable Biolimus Stent Appears Safe and Effective in PCI - Jacobson, Anne (MD Conference Express, 2008)
A new generation of drug-eluting stent that is coated with biolimus and released from a biodegradable polymer demonstrated similar safety and efficacy through 9 months as compared with stents releasing sirolimus from a durable polymer in patients who were undergoing percutaneous coronary intervention, according to findings from the Limus Eluted from A Durable versus ERodable Stent [LEADERS] trial.